To solve the system of linear equations 8 x + 5 y = 18 and 6 x + y = negative 2. by using the linear combination method, Amos decided that he should first multiply the second equation by –5 and then add the two equations together to eliminate the y-terms. His calculations are as shown.

8 x + 5 y = 18. + 6 x minus 5 y = 10. 14 x = 28. StartFraction 14 x Over 14 EndFraction = StartFraction 28 Over 14 EndFraction. X = 2.

6 x + y = negative 2. 6 (2) + y = negative 2. 12 + y = negative 2. 12 + y minus 12 = negative 2 minus 12. y = negative 14.

Amos’s solution is (2, –14). What did he do wrong?
He multiplied the equation 6 x + y = negative 2. by –5 incorrectly.
He added the equations 8 x + 5 y = 18 and 8 x + 5 y = 18 incorrectly.
He substituted 2 into the equation 6 x + y = negative 2. incorrectly.
He solved the equation 12 + y = negative 2 for y incorrectly.

1 answer

Let's examine Amos's solution step by step and identify any mistakes.

  1. Starting with the equations:

    • Equation 1: \( 8x + 5y = 18 \)
    • Equation 2: \( 6x + y = -2 \)
  2. Amos correctly decided to multiply the second equation by -5: \[ -5(6x + y) = -5(-2) \implies -30x - 5y = 10 \]

  3. Now we have:

    • Equation 1: \( 8x + 5y = 18 \)
    • Modified Equation 2: \( -30x - 5y = 10 \)
  4. Next, when he added the two equations to eliminate \(y\): \[ (8x + 5y) + (-30x - 5y) = 18 + 10 \implies -22x = 28 \] Therefore, simplifying gives: \[ -22x = 28 \implies x = \frac{28}{-22} \implies x = -\frac{14}{11} \quad (\text{or approximately } -1.273) \]

  5. Now, substituting \( x = 2 \) into: \[ 6x + y = -2 \implies 6(2) + y = -2 \implies 12 + y = -2 \implies y = -2 - 12 = -14 \]

However, this substitution assumes \( x = 2 \) was correct, but we've already shown that the calculation for \(x\) was incorrect.

To summarize:

  • The error occurred when Amos added the equations. He should have derived \( -22x = 28 \) from the addition, which indicates a calculation mistake in the use of coefficients, leading to the false conclusion that \( x = 2 \).

The final answer: He solved the equation incorrectly when trying to eliminate \(y\) with the incorrect addition of the equations.